ECONOMIC LITERACY AND ECONOMIC DECISIONS - Budiwati, Neti; Hilmiatussadiah, Kinanti Geminastiti; Nuriansyah, Fazar; Nurhayati, Dwi (JURNAL PENDIDIKAN ILMU SOSIAL, 2020)
This study investigates social studies learning is a scientific field that cannot be separated from its role in solving problems that occur in society. Students will participate as agents of change in society that have knowledge, insights, attitudes, and understandings that are upholding sustainability.Social studies need more authentic learning, which simulates a real-world environment by making it a source and a medium of learning, so that the context and allowance are used with similar situations, meaningful and connected to the real world by applying transdisciplinary learning. This paper contains a literature review on the application of learning in social studies learning to prepare students to live in harmony with the sustainable living. This literature study refers to the theoretical aspects of transdisciplinary learning, social studies within transdisciplinary learning, and learning outcomes related to sustainable living.